2020
DOI: 10.1093/milmed/usz426
|View full text |Cite
|
Sign up to set email alerts
|

Use of Lean Six Sigma to Improve Access to Care in a Surgical Subspecialty Clinic

Abstract: Introduction At the Naval Medical Center San Diego urology clinic, patients reported waiting for greater than 1 month for an initial consult. A Lean Six Sigma approach was used to improve access to care (ATC) and decrease variation in access by improving scheduling. Methods A Define-Measure-Analyze-Improve-Control approach was used. Delay to new patient visits was identified as the focus of intervention. The scheduling templa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…To the best of our knowledge, the present study is the first to investigate the effects of Six Sigma methodology on the incidence of depression and anxiety in ESRD patients. Previous studies have confirmed that Six Sigma methodology could improve the timeliness of care and the overall quality of nursing care in several departments (21,22). We then modified conventional Six Sigma methodology and added some cognitive-behavioral therapy into it to focus on the improvement of psychological conditions in ESRD patients.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the present study is the first to investigate the effects of Six Sigma methodology on the incidence of depression and anxiety in ESRD patients. Previous studies have confirmed that Six Sigma methodology could improve the timeliness of care and the overall quality of nursing care in several departments (21,22). We then modified conventional Six Sigma methodology and added some cognitive-behavioral therapy into it to focus on the improvement of psychological conditions in ESRD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Balancing patient quality of care and efficiency is an ongoing issue in healthcare, with clinic workflows hampered or negatively impacted for a variety of reasons. This may include poor or inadequate space or work layouts, and/or excessive workload resulting from inefficiencies in work processes, factors which can increase patient wait times and may lead to provider burnout (Flanary et al, 2020). Quality Improvement (QI) studies are focused on improving these types of conditions and can take many forms.…”
Section: Issues With Clinical Workflow Healthcare Environments and Wait Timesmentioning
confidence: 99%
“…Quality Improvement (QI) studies are focused on improving these types of conditions and can take many forms. Some QI methods that have been used to increase efficiency and reduce wait times include eliminating automatic rebooking or overbooking, adjusting the ratio of new patient visits to follow-up visits, and increasing the use of physician assistants (Flanary et al, 2020). This QI study aimed to reveal potential bottlenecks that may be impacting the overall workflow of the Genetics Clinic, with a particular focus on the work of GCs in patient workflows.…”
Section: Issues With Clinical Workflow Healthcare Environments and Wait Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some QI methods that have been used to increase efficiency and reduce wait times include eliminating automatic rebooking or overbooking, adjusting the ratio of new patient visits to follow-up visits, and increasing the use of physician assistants (Flanary et al, 2020). The concept of Quality Improvement using structured methods began in the manufacturing industry and are now being applied to in healthcare (Lin et al, 2013).…”
Section: Common Approaches To Improve Clinical Workflowmentioning
confidence: 99%